Impact of maternal protein restriction on the proteomic landscape of male rat lungs across the lifespan - Naia Fioretto, Matheus [UNESP]; Maciel, Flávia Alessandra [UNESP]; Barata, Luísa Annibal [UNESP]; Ribeiro, Isabelle Tenori [UNESP]; Basso, Carolina Beatriz Pinheiro [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; dos Santos, Sérgio Alexandre Alcantara [UNESP]; Mattos, Renato [UNESP]; Baptista, Hecttor Sebastian [UNESP]; Portela, Luiz Marcos Frediane [UNESP]; Padilha, Pedro Magalhães [UNESP]; Felisbino, Sérgio Luis [UNESP]; et al. (Elsevier, 2024)
The developmental origins of healthy and disease (DOHaD) concept has demonstrated a higher rate of chronic diseases in the adult population of individuals whose mothers experienced severe maternal protein restriction (MPR). Using proteomic and in silico analyses, we investigated the lung proteomic profile of young and aged rats exposed to MPR during pregnancy and lactation. Our results demonstrated that MPR lead to structural and immune system pathways changes, and this outcome is coupled with a rise in the PI3k-AKT-mTOR signaling pathway, with increased MMP-2 activity, and CD8 expression in the early life, with long-term effects with aging. This led to the identification of commonly or inversely differentially expressed targets in early life and aging, revealing dysregulated pathways related to the immune system, stress, muscle contraction, tight junctions, and hemostasis. We identified three miRNAs (miR-378a-3p, miR-378a-5p, let-7a-5p) that regulate four proteins (ACTN4, PPIA, HSPA5, CALM1) as probable epigenetic lung marks generated by MPR. In conclusion, MPR impacts the lungs early in life, increasing the possibility of long-lasting negative outcomes for respiratory disorders in the offspring.
Keywords: Aging; Early life; Lungs; Maternal malnutrition; Proteomics